2019
DOI: 10.1029/2018gc007985
|View full text |Cite
|
Sign up to set email alerts
|

“Petit Spot” Rejuvenated Volcanism Superimposed on Plume‐Derived Samoan Shield Volcanoes: Evidence From a 645‐m Drill Core From Tutuila Island, American Samoa

Abstract: In 2015 a geothermal exploration well was drilled on the island of Tutuila, American Samoa. The sample suite from the drill core provides 645 m of volcanic stratigraphy from a Samoan volcano, spanning 1.45 million years of volcanic history. In the Tutuila drill core, shield lavas with an EM2 (enriched mantle 2) signature are observed at depth, spanning 1.46 to 1.44 Ma. These are overlain by younger (1.35 to 1.17 Ma) shield lavas with a primordial “common” (focus zone) component interlayered with lavas that sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(41 citation statements)
references
References 103 publications
2
39
0
Order By: Relevance
“… Diagram of the principal component analysis (PCA) of geochemical proxies used in Figures 5, 6 and 9 (Sr‐Nd‐Pb‐He isotopes, Ba/Th, Ba/Ta, La/Ta, Zr/Hf, and Zr/Th in right panel). Samples from the shield‐stage and rejuvenated Samoa (open symbols represent data from Konter & Jackson, 2012; filled symbols represent data from Reinhard et al., 2019) and the Pitcairn (Eisele et al., 2002) are included in a source data for the PCA. The enriched CSR basalts have high Ba/Th and Ba/Ta ratios similar to the South Pandora Ridge and Wallis samples.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… Diagram of the principal component analysis (PCA) of geochemical proxies used in Figures 5, 6 and 9 (Sr‐Nd‐Pb‐He isotopes, Ba/Th, Ba/Ta, La/Ta, Zr/Hf, and Zr/Th in right panel). Samples from the shield‐stage and rejuvenated Samoa (open symbols represent data from Konter & Jackson, 2012; filled symbols represent data from Reinhard et al., 2019) and the Pitcairn (Eisele et al., 2002) are included in a source data for the PCA. The enriched CSR basalts have high Ba/Th and Ba/Ta ratios similar to the South Pandora Ridge and Wallis samples.…”
Section: Discussionmentioning
confidence: 99%
“…no depletion of HFSE such as Nb and Ta, Figure 3) cannot be attributed to the typical sub-arc mantle, Instead, the Ba-rich characteristic of the enriched CSR basalts is similar to those of the Gaussberg lamproite in Antarctica and the Cenozoic alkaline basalts in NE China, which is considered to have originated from the OH ET AL. Reinhard et al (2019), and (c) Ba/Ta versus La/Ta modified from Gorring et al (2003). Symbols are the same as in Figure 1c.…”
Section: Upper Mantle Upwelling Induced By a Stagnant Slab In The Mantle Transition Zonementioning
confidence: 99%
See 1 more Smart Citation
“…At Samoa, subaerial rejuvenated volcanism occurs on the islands of Savai‘i, Upolu, and Tutuila, which are located >180 km from the current location of the Samoan mantle plume (which is inferred to lie below the volcanically active Vailulu‘u seamount). The source of rejuvenated volcanism at Samoa is not well understood, but has been discussed elsewhere (Konter & Jackson, 2012; Natland, 1980; Workman et al., 2004; Reinhard et al., 2019). It has been proposed that rejuvenated volcanism at Samoa may be driven by mantle melting from plate flexure of the lithosphere due to subduction at the Tonga Trench (Konter & Jackson, 2012; Natland, 1980).…”
Section: Discussionmentioning
confidence: 99%
“…Second, Samoa is located near the Tonga Trench, and there is evidence for interaction between the Samoan plume and this subducting zone that could influence the age progression recorded at this location (Hart et al, 2004;Koppers et al, 2008). Here chemical interactions between the Samoan plume and the down going slab have been linked to late-stage volcanism on Samoa (Konter & Jackson, 2012;Price et al, 2016;Reinhard et al, 2019). Modeling has shown that tectonic interactions in the Tonga Trench may be causing plate tearing that allows for magma to penetrate the lithosphere (Govers & Wortel, 2005) as well as distortions in local mantle flow (Druken et al, 2014) that both may cause different volcanic surface expressions compared to the traditional mantle plume theory.…”
Section: Analysis Of Absolute Plate Motion Modelsmentioning
confidence: 99%